Delineation and estimation of unsaturated aquifer and saturated aquifer of Faridabad district, Haryana, India - THAMAR, ABDUL RAHMAN; SHERRING, ARPAN; AHSAN, MD JAFRI (Journal of Soil and Water Conservation, 2020)
India in general and Faridabad in particular is facing a serious water resource problem and as trends suggest, it is expected to become ‘water stressed’ by 2025 and ‘water scarce’ by 2050 (IDSA, 2010). The Faridabad district is critically reliant on groundwater for both drinking water and non–potable uses. The area comprises both rural and urban area. Better understanding of groundwater flow, identification of recharge and discharge area will ensure sustainability of groundwater resources. ArcGIS (ESRI, USA) is a geographic information system (GIS) for working with maps and geographic information. It is used for creating and using maps; compiling geographic data; analyzing spatial information and managing database in GIS platform. It is used for making DEM, water table contour map interpolation, spatial analysis and raster analysis etc. This has resulted in increased groundwater draft for construction purpose and further leading to decline of water level. The close inspection of four hydrographs reveals that there is distinct pattern in hydrograph behaviour. Ballabhgarh and Bhoapni indicates sharp decline in water level because these monitoring wells lies in urban area. Whereas Kabulpur and Sikri water level is almost constant as these two well fall in rural/agricultural area. In urabn area paved area restricts recharge whereas in rural area return flow from irrigation recharge the aquifer. In order to assess the aquifer volume available for recharge GIS based analysis was carried out. Post Monsoon water level is used to estimate unsaturated thickness of aquifer which is available for recharge. Water level more than 3 meter has been considered as maximum water level for recharge above this it will create water logging condition.